α-Cyperone Confers Antidepressant-Like Effects in Mice via Neuroplasticity Enhancement by SIRT3/ROS Mediated NLRP3 Inflammasome Deactivation - Xia, Baomei; Tong, Yue; Xia, Changbo; Chen, Chang; Shan, Xin (Frontiers in Pharmacology, 2020)
α-Cyperone (Cy) is a major active compound of Cyperus rotundus that has various pharmacological activities. But whether Cy possesses antidepressant effect is unknown. In this study, we exposed mice to chronic unpredictable mild stress (CUMS) with or without intervention with Cy. Our results showed that Cy significantly improved the depressive phenotypes in sucrose preference test, tail suspension test and forced swimming test. Meanwhile, increased SIRT3 expression, reduced ROS production and activated NF-κB signal were detected in the hippocampus of mice. NLRP3 inflammasome related proteins including NLRP3, ASC, Caspase-1, IL-1β, IL-18 and GSDMD-N were downregulated after Cy administration. Synaptic proteins including Synapsin-1 and PSD-95 and dendritic spine density were improved after Cy treatment. Moreover, the protective effects of Cy in CUMS mice were compromised when co-administrated with SIRT3 inhibitor 3-TYP. Taken together, these findings suggested that Cy has therapeutic potential for treating depression and that this antidepressant effect may be attributed to SIRT3 stimulated neuroplasticity enhancement by suppressing NLRP3 inflammasome.